Using Bloom’s taxonomy to assess social media assignments - Sylvia IV, J.J. (Journal of Interdisciplinary Studies in Education, 2019)
This paper argues that by linking social media assignments to particular levels ofBloom’s Taxonomy, instructors can more easily and straightforwardly assessassignments. Much confusion exists over how to best incorporate these tools, andfurther, how to properly assess student performance related to social media.Often social media is used simply as an additional and optional channel ofcommunication, rather than as an inherent part of a graded assignment, due inpart to the difficulties of assessment. Using social media effectively andcollaboratively is an important aspect of literacy in the 21st century; it is thereforeimportant to move beyond merely incorporating the tools, but also assessing theuse of the tools